Transformational leadership, transnational culture and political competence in globalizing health care services: a case study of Jordan's King Hussein Cancer Center - Pappas Gregory; Moe Jeffrey L; Murray Andrew (BMC, 2007)
Abstract Background Following the demise of Jordan's King Hussein bin Talal to cancer in 1999, the country's Al-Amal Center was transformed from a poorly perceived and ineffectual cancer care institution into a Western-style comprehensive cancer center. Renamed King Hussein Cancer Center (KHCC), it achieved improved levels of quality, expanded cancer care services and achieved Joint Commission International accreditation under new leadership over a three-year period (2002-2005). Methods An exploratory case research method was used to explain the rapid change to international standards. Sources including personal interviews, document review and on-site observations were combined to conduct a robust examination of KHCC's rapid changes. Results The changes which occurred at the KHCC during its formation and leading up to its Joint Commission International (JCI) accreditation can be understood within the conceptual frame of the transformational leadership model. Interviewees and other sources for the case study suggest the use of inspirational motivation, idealized influence, individualized consideration and intellectual stimulation, four factors in the transformational leadership model, had significant impact upon the attitudes and motivation of staff within KHCC. Changes in the institution were achieved through increased motivation and positive attitudes toward the use of JCI continuous improvement processes as well as increased professional training. The case study suggests the role of culture and political sensitivity needs re-definition and expansion within the transformational leadership model to adequately explain leadership in the context of globalizing health care services, specifically when governments are involved in the change initiative. Conclusion The KHCC case underscores the utility of the transformational leadership model in an international health care context. To understand leadership in globalizing health care services, KHCC suggests culture is broader than organizational or societal culture to include an informal global network of medical professionals and Western technologies which facilitate global interaction. Additionally, political competencies among leaders may be particularly relevant in globalizing health care services where the goal is achieving international standards of care. Western communication technologies facilitate cross-border interaction, but social and political capital possessed by the leaders may be necessary for transactions across national borders to occur thus gaining access to specialized information and global thought leaders in a medical sub-specialty such as oncology.